Peran Kebudayaan Religius di Sekolah Terhadap Perkembangan Kecerdasan Spiritual Siswa (Studi Kasus Madrasah Pembangunan UIN Jakarta) - Muhammad Ihsan Nashihin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The school has important role to improve the quality of students. Not only in intelectual side but also for improving the quality of spiritual and piety os students. This research aims to analyse how the influence of the school environment can affect the development of spiritual quotient of student in Madrasah Pembangunan UIN Jakarta. The study method used quantitative method. The author used field research method to gain the firm and secondary data. The data collection techniques was taken by spreading questionnaire for 90 students, observation and collecting the important document. This study found that there was positive influence of the religious culture in the school could affect the positive influence in betta coefficients rate 0,372 (37%) into development of stydent’s spiritual quotient. The religious culture is unofficial effort of education out of the class containing : religious activity (duha, prayer, jama’ah prayer), good attitude among students and teacher, kind culture in the school. It suggests to all teacher to improve the religious culture in the school to make students more religious and get development of spiritual quotient.Keywords – Hidden Curriculum, Kebudayaan Religius, Kecerdasan Spiritual.